Novel phase change energy lattice and preparation method thereof
Through powder composite fixed phase transformation system and macroscopic secondary packaging technology, the problems of liquid leakage, easy phase separation and poor flame retardancy of existing phase transformation energy storage materials during phase transformation are solved, and the stability and efficient circulation performance of the materials are achieved, and it is suitable for building energy conservation and battery thermal management.
Patent Information
- Application Number
- CN202411860805.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-17
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2044-12-17
AI Technical Summary
During the phase change process, existing phase change energy storage materials are prone to fluid leakage, easy phase separation, poor flame retardancy and poor circulation performance, resulting in potential safety hazards in actual applications.
The powder-like composite fixed phase transformation system is adopted to adsorb phase transformation substrates and additives by modifying the support framework material to form a stable fixed phase transformation material, and package it in aluminum foil bags and other enclosed bags through macroscopic secondary packaging to solve the liquid leakage problem.
The physical and chemical properties of phase change materials are achieved, the problems of phase separation and liquid leakage are reduced, the flame retardant and circulation performance are improved, and the material synthesis process is simple and the product is easy to apply.
Smart Images

Figure CN119570455A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a novel phase-change energy lattice and a preparation method thereof, and belongs to the technical field of phase-change energy storage materials. Background Art
[0002] Phase change energy storage materials refer to materials that reach their phase change temperature during the heating (or cooling) process, absorb (or release) a large amount of heat from the environment, and maintain a constant temperature for a period of time. According to the different phase states, they can be divided into solid-solid phase change materials, solid-liquid phase change materials, solid-gas phase change materials, and liquid-gas phase change materials; according to the chemical composition, phase change materials can be divided into organic phase change materials, inorganic phase change materials, and composite phase change materials. At present, solid-liquid phase change materials are the most studied.
[0003] Organic solid-liquid materials have low supercooling and good cyclicity, but are extremely easy to burn. Inorganic solid-liquid phase change materials have good flame retardancy and high enthalpy value, but there is a problem of easy phase separation. At the same time, the inevitable leakage problem of organic and inorganic solid-liquid phase change materials during the phase change process is one of the main factors hindering their practical application. One way to prevent leakage is to use the phase change material as the core material and the polymer as the shell material for encapsulation. This method has high preparation costs and is not conducive to large-scale application. Another method is to use porous materials for encapsulation, such as fumed silica, expanded vermiculite, etc. Using porous materials to shape and encapsulate the phase change material can alleviate the leakage problem, but because it only relies on capillary forces, the adsorption rate is low and the phase change material is easy to seep out of the pores, so the composite material has poor long-term stability. And the shaped phase change material still has problems of pressure difference, poor cyclic stability, and long-term leakage in practical applications.
[0004] During the phase change process of gel-like phase change materials, the movement and rearrangement of molecular chains are relatively difficult, and supercooling is prone to occur, that is, the material begins to change phase when it is cooled below its theoretical phase change temperature. In addition, gel-like materials have certain viscosity and elasticity, and poor fluidity. In some application scenarios that require tight filling or complex shapes, it is difficult to fill the space evenly, which may cause uneven local heat transfer. During long-term use, gel-like phase change materials may experience problems such as degradation and aging of the gel structure, resulting in a decrease in their performance; and the cycle performance is poor. After multiple phase change cycles, the gel structure of the gel-like phase change material may be damaged, resulting in problems such as reduced latent heat of phase change and poor thermal conductivity. Summary of the invention
[0005] In order to solve the problems existing in the prior art, the present invention provides a preparation of a new type of phase change energy grid. The new phase change energy grid prepared by the present invention has a suitable phase change temperature and a high phase change enthalpy value. The fluidity of the material after phase change is reduced by a modified supporting skeleton through one-time adsorption. The organic-inorganic composite can reduce the phase separation and improve the flame retardancy. Further, through macroscopic secondary packaging, the leakage problem in the phase change process is effectively solved. Compared with gel-like phase change materials, the physical and chemical properties of the powdered phase change materials in this application are relatively stable, and it is not easy to deteriorate or perform attenuate during long-term use. The particles of the powdered phase change materials are relatively stable during the phase change cycle and can maintain good cycle performance. The material in this energy pack is in powder form, which is easier to fill during the reproduction process, and the application process is more stable and long-lasting. The material synthesis process is simple, the product is easy to use, and it has broad application prospects.
[0006] The technical solution of the present invention is as follows:
[0007] A novel phase change energy grid is prepared, which is composed of a composite shape-fixed phase change system with thermal energy storage performance and an encapsulation bag. The composite shape-fixed phase change system is obtained by compounding a hydrophilic shape-fixed phase change system and a lipophilic phase change system, and the hydrophilic and lipophilic phase change systems include a modified support skeleton material, a phase change substrate and an additive.
[0008] In the above technical scheme, the ratio of hydrophilic and lipophilic phase change systems in the composite shaped phase change system is 2:8~8:2, wherein the mass proportion of the modified supporting skeleton material is 30%~1%, the mass proportion of the phase change substrate is greater than or equal to 50% and less than 99%, and the proportion of the auxiliary agent is greater than zero and less than or equal to 20%.
[0009] In the above technical solution, the packaging bag is one of an aluminum foil bag, a tin foil bag, a copper foil bag, a PET bag, a PE bag, a polytetrafluoroethylene bag, and a polypropylene bag.
[0010] The modified support skeleton material includes a hydrophilic modified support skeleton and an oleophilic modified support skeleton, and the hydrophilic and hydrophobic modification methods include but are not limited to surface sintering, acid-base reaction, chemical grafting and gas phase reaction. The modified support skeleton material is one or more of porous silica, expanded vermiculite, diatomaceous earth, expanded perlite, expanded graphite, activated carbon, porous carbon, bentonite and porous ceramics modified by hydrophilic or oleophilic methods.
[0011] In the above technical scheme, the phase change substrate is one or more of sodium carbonate decahydrate, sodium sulfate decahydrate, calcium chloride hexahydrate, disodium hydrogen phosphate dodecahydrate, sodium acetate trihydrate, copper sulfate heptahydrate, magnesium sulfate heptahydrate, disodium hydrogen phosphate heptahydrate, barium hydroxide octahydrate, potassium aluminum sulfate dodecahydrate, paraffin, tetradecane, hexadecane, octadecane, eicosane, decanoic acid, dodecanoic acid, tetradecanoic acid, pentadecanoic acid, palmitic acid, stearic acid, dodecanol, tetradecanol, hexadecanol, octadecyl alcohol, polyethylene glycol with a molecular weight of 200 to 20,000, xylitol, sorbitol, erythritol tetrapalmitate, galactitol hexapalmitate, galactitol hexastearate, tristearin, tripalmitin, trimyristin, butyl stearate, soybean oil, corn oil, peanut oil, rapeseed oil, olive oil, and castor oil.
[0012] In the above technical scheme, the auxiliary agent is one or more of water, carboxymethyl cellulose, sodium carboxymethyl cellulose, sodium alginate, xanthan gum, carrageenan, polyacrylic acid, sodium polyacrylate, sodium metasilicate nonahydrate, dimethyl fumarate, diethyl fumarate and dibutyl fumarate, fumaric acid, benzoic acid, sodium benzoate, para-chloro-meta-xylenol, salicylanilide and tetrachlorophenol, pentachlorophenol, sorbic acid and its salts, chloroacetic acid, halogenated phenoxyacetic acid, alkyl thiocyanate, halogenated salicylic acid, thiosalicylic acid, sodium chlorite, iodide, boric acid and its salts, sulfites and pyrosulfites, and sodium nitrite.
[0013] The present invention also provides a method for preparing the novel energy grid, comprising the following steps:
[0014] (1) The hydrophilic and lipophilic phase change substrates are heated and melted at 50-80°C, respectively, and magnetically stirred for 0.5-2 hours to form a uniform liquid.
[0015] (2) Adding the additive and the modified supporting skeleton material to the phase change substrate in the molten state in step (1), the hydrophilic modified skeleton material adsorbs the hydrophilic phase change substrate, and the lipophilic modified skeleton material adsorbs the lipophilic phase change substrate, and stirring is continued during the process to ensure uniform mixing.
[0016] (3) The composite materials in step (2) are placed in a vacuum drying oven at 50°C to 80°C and heated to obtain a hydrophilic shape-fixed phase change system and a lipophilic phase change system.
[0017] (4) The prepared hydrophilic shape-fixing phase change system and lipophilic phase change system are repeatedly mixed evenly, put into a packaging bag, and sealed with a hot press to obtain a new phase change energy grid.
[0018] Beneficial effects of the present invention: The present invention provides a method for preparing a novel phase change energy grid, which consists of a composite shaped phase change system with thermal energy storage performance and an encapsulation bag. The powdery composite shaped phase change material in the present application is a complete technical solution obtained by the cooperation and interaction of the modified support skeleton material, the phase change substrate and the auxiliary agent, and the various parts are synergistic; the modified support skeleton material is used to adsorb the phase change substrate and the auxiliary agent to obtain a shaped phase change material with stable morphology; the organic and inorganic phase change system is used to composite, and the phase separation is reduced while the flame retardant performance is improved; the addition of the auxiliary agent can reduce the phase separation, water loss and fluidity problems of the phase change substrate. At the same time, the encapsulation bag is used to realize the secondary packaging of the composite phase change system to obtain a novel phase change energy grid. The powdery composite shaped phase change material is encapsulated in the encapsulation bag, and the particles have a large specific surface area, and can exchange heat with the surrounding environment faster when the temperature changes, and the supercooling is relatively small. And the powdery phase change material has good fluidity and can be better filled into the encapsulation bag. This energy grid not only has a simple synthesis process, but is also pressure-resistant, wear-resistant, leak-free, and easy to use. Therefore, it has broad application prospects in the fields of building energy conservation, battery thermal management, etc. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 This is the energy grid product in Example 1.
[0020] Figure 2 This is the DSC curve of the composite shape-fixed phase change system in Example 1.
[0021] Figure 3 This is the DSC curve of the composite shape-fixed phase change system in Example 2.
[0022] Figure 4 This is the DSC curve of the composite shape-fixed phase change system in Comparative Example 2 before and after 50 cycles. DETAILED DESCRIPTION
[0023] The following non-limiting examples are provided to enable those skilled in the art to more fully understand the present invention, but are not intended to limit the present invention in any way. The experimental methods described in the following examples are conventional methods unless otherwise specified; the reagents and materials described are commercially available unless otherwise specified.
[0024] A novel phase-change energy grid, which uses a powdered composite shaped phase-change material with thermal energy storage performance encapsulated in an encapsulation bag;
[0025] The composite shape-fixed phase change material is obtained by compounding a hydrophilic shape-fixed phase change system and a lipophilic phase change system. The hydrophilic shape-fixed phase change system and the lipophilic phase change system respectively include a modified supporting skeleton material, a phase change substrate and an additive; the hydrophilic shape-fixed phase change system includes a hydrophilic modified supporting skeleton material, a phase change substrate and an additive, and the lipophilic phase change system includes a lipophilic modified supporting skeleton material, a phase change substrate and an additive.
[0026] The ratio of hydrophilic shaped phase change material to lipophilic phase change system in the composite shaped phase change system is 2:8~8:2. The principle of selecting the ratio of hydrophilicity to lipophilicity is to adjust it according to the requirements of the application scenario for phase change temperature, flame retardancy and other properties, such as 2:8, 3:7, 4:6, 5:5, 7:3, 8:2. Among them, the mass proportion of modified support skeleton material is 30% to 1%, such as 1%, 2%, 5%, 8%, 15%, 20%, 30%, etc. The mass proportion of phase change substrate is greater than or equal to 50% and less than 99%, such as 50%, 70%, 80%, 90%, 95%, etc. The proportion of additives is greater than zero and less than or equal to 20%, such as 2%, 5%, 8%, 10%, etc.
[0027] The encapsulation bag is a macro packaging for encapsulating powdered composite shaped phase change materials. It is required to have good sealing properties to prevent leakage and block foreign substances; it also has suitable mechanical properties, and the encapsulation bag cannot be easily scratched or torn during daily handling, installation and use. Good thermal conductivity, so that it can quickly absorb and release heat, and at the same time be able to withstand the corresponding high temperature without losing its sealing and mechanical properties. It must also have chemical compatibility and will not react chemically with the phase change material. Good processing performance, easy to form and package, can ensure the consistency and stability of quality during the packaging process, and can be mass-produced. The encapsulation bag can be selected from one of aluminum foil bags, tin foil bags, copper foil bags, PET bags, PE bags, polytetrafluoroethylene bags, and polypropylene bags according to the above performance requirements.
[0028] In order to improve the compatibility with phase change materials, increase thermal conductivity, improve the stability and cycle performance of materials, the modified support skeleton material is modified to be hydrophilic and lipophilic to the original skeleton material; the modified support skeleton material includes a hydrophilic modified support skeleton and a lipophilic modified support skeleton. The hydrophilic modified support skeleton is used in the hydrophilic shaped phase change material, and the lipophilic modified support skeleton is used in the lipophilic phase change system; the modification methods include surface sintering, acid-base reaction, chemical grafting and gas phase reaction, etc. The modified support skeleton material is one or more of porous silica, expanded vermiculite, diatomaceous earth, expanded perlite, expanded graphite, activated carbon, porous carbon, bentonite, and porous ceramics that have been hydrophilically or lipophilically modified.
[0029] The phase change substrate is the core of the powdered composite shaped phase change material, playing a core role in energy storage. It also determines the phase change temperature and latent heat characteristics, affecting the stability and cycle life of the material. At the same time, it plays a synergistic role with other ingredients. The phase change substrate usually cooperates with other additives (such as supporting skeletons, stabilizers, thermal conductivity enhancers, etc.). The properties of the phase change substrate will affect how it interacts with these additives. The phase change substrate is a hydrophilic phase change substrate and a lipophilic phase change substrate. The hydrophilic phase change substrate is one or more of sodium carbonate decahydrate, sodium sulfate decahydrate, calcium chloride hexahydrate, disodium hydrogen phosphate dodecahydrate, sodium acetate trihydrate, copper sulfate heptahydrate, magnesium sulfate heptahydrate, disodium hydrogen phosphate heptahydrate, barium hydroxide octahydrate, and potassium aluminum sulfate dodecahydrate; the lipophilic phase change substrate is one or more of paraffin, tetradecane, hexadecane, octadecane, eicosane, decanoic acid, dodecanoic acid, tetradecanoic acid, pentadecanoic acid, palmitic acid, stearic acid, dodecanol, tetradecanol, hexadecanol, octadecyl alcohol, polyethylene glycol with a molecular weight of 200 to 20,000, xylitol, sorbitol, erythritol tetrapalmitate, galactitol hexapalmitate, galactitol hexastearate, tristearin, tripalmitin, trimyristin, butyl stearate, soybean oil, corn oil, peanut oil, rapeseed oil, olive oil, and castor oil.
[0030] In order to generate powdery composite shaped phase change materials and improve the performance of phase change materials, it is necessary to use corresponding additives on the basis of phase change substrates and modified support skeletons; these additives may play the following roles: in improving the cyclicity of phase change materials, they can promote the crystallization of phase change materials, reduce supercooling and phase separation, and prevent the degradation of phase change performance due to water loss of crystallization water; improve thermal conductivity or adjust phase change temperature and latent heat. In terms of enhancing physical properties, enhance stability: volume changes may occur during the phase change process, and additives can stabilize the structure; they can also improve fluidity and filling properties. In terms of improving chemical properties, they can improve chemical stability and material compatibility. The auxiliary agents used are one or more of water, carboxymethyl cellulose, sodium carboxymethyl cellulose, sodium alginate, xanthan gum, carrageenan, polyacrylic acid, sodium polyacrylate, sodium metasilicate nonahydrate, dimethyl fumarate, diethyl fumarate, dibutyl fumarate, fumaric acid, benzoic acid, sodium benzoate, para-chloro-meta-xylenol, salicylanilide and tetrachlorophenol, pentachlorophenol, sorbic acid and its salts, chloroacetic acid, halogenated phenoxyacetic acid, alkyl thiocyanate, halogenated salicylic acid, thiosalicylic acid, sodium chlorite, iodide, boric acid and its salts, sulfites and pyrosulfites, and sodium nitrite.
[0031] The preparation method of the novel phase change energy grid comprises the following steps:
[0032] (1) heating and melting the hydrophilic phase change substrate and the lipophilic phase change substrate at 50 to 80° C. respectively, and magnetically stirring for 0.5 to 2 h to form a uniform liquid;
[0033] (2) adding the auxiliary agent and the hydrophilic modified supporting skeleton material to the hydrophilic phase change substrate in the molten state in step (1), and the hydrophilic modified skeleton material adsorbs the hydrophilic phase change substrate; adding the auxiliary agent and the lipophilic modified supporting skeleton material to the lipophilic phase change substrate in the molten state in step (1), and the lipophilic modified skeleton material adsorbs the lipophilic phase change substrate; stirring continuously during the process to ensure uniform mixing;
[0034] (3) placing the materials in step (2) in a vacuum drying oven at 50°C to 80°C and heating them to obtain a hydrophilic shape-fixed phase change system and a lipophilic phase change system;
[0035] (4) The prepared hydrophilic shape-fixing phase change system and lipophilic phase change system are mixed evenly in proportion, put into a packaging bag, and sealed with a hot press to obtain a new phase change energy grid.
[0036] Example 1
[0037] Sodium carbonate decahydrate and disodium hydrogen phosphate dodecahydrate were weighed in a mass ratio of 5:5, placed in a 20 mL glass bottle, heated and stirred at 50°C for 1 hour to mix the two evenly, and 2% sodium metasilicate nonahydrate, 5% water, 1% carboxymethyl cellulose and 2% sodium benzoate were added thereto; the above phase change substrate and additives were compounded with polyvinyl alcohol modified diatomite by vacuum impregnation, and after compounding, placed in a vacuum drying oven at 60°C for heating to obtain a powdered hydrophilic shaped phase change system. Among them, the mass ratio of the phase change substrate to the polyvinyl alcohol modified diatomite is 80:10.
[0038] The 25-degree phase-change paraffin wax was heated and melted at 50°C, 2% sodium benzoate was added thereto, and after being mixed evenly, it was compounded with the porous carbon modified by PDMS vapor deposition by vacuum impregnation. The porous carbon modified by PDMS vapor deposition was obtained by mixing PDMS and porous carbon at a mass ratio of 1:3 at 250°C and depositing them in a vapor deposition device for 1 hour. After compounding, it was placed in a vacuum drying oven at 60°C and heated to obtain a powdered lipophilic shaped phase change system. The mass ratio of paraffin wax to modified porous carbon was 90:8.
[0039] The prepared hydrophilic shape-fixed phase change system and the lipophilic shape-fixed phase change system are mixed in a ratio of 2:8 to obtain a powdery composite shape-fixed phase change material, which is packaged in an aluminum foil bag to obtain an energy grid with phase change characteristics.
[0040] Figure 1 The new phase change energy grid product is completely sealed with a hot press, which effectively solves the leakage problem of phase change materials. It is easy to use and can be directly applied to scenarios that require thermal management. Figure 2This is the DSC curve of the composite shape-fixed phase change system in the phase change energy grid in Example 1, with a phase change temperature of 23.6° C. and a phase change enthalpy of 158.5 J / g, which has a suitable phase change temperature and a high phase change enthalpy.
[0041] Example 2
[0042] Sodium sulfate decahydrate and disodium hydrogen phosphate dodecahydrate were weighed in a mass ratio of 6:4, heated and stirred at 50°C for 1h to mix the two evenly, and 2% sodium metasilicate nonahydrate, 5% deionized water, 1% sodium alginate and 2% potassium sorbate were added thereto, and heated and stirred at 50°C for 0.5h to mix the components evenly; the above phase change substrate was compounded with polyvinyl alcohol modified diatomite, and after compounding, it was placed in a vacuum drying oven at 60°C for heating to obtain a hydrophilic fixed phase change system. Among them, the mass ratio of the phase change substrate to the polyvinyl alcohol modified diatomite is 80:10.
[0043] Octadecane and eicosane were weighed in a mass ratio of 7:3, heated and melted at 50°C, 2% sodium benzoate was added thereto, mixed evenly, and then composited with PDMS vapor deposition modified porous carbon by vacuum impregnation. The PDMS vapor deposition modified porous carbon was obtained by mixing PDMS and porous carbon in a mass ratio of 1:3 and depositing them in a vapor deposition device for 1 hour at 250°C. After composite, it was placed in a vacuum drying oven at 60°C and heated to obtain an oleophilic shaped phase change system in which the mass ratio of paraffin wax to modified porous carbon was 90:8.
[0044] The prepared hydrophilic shape-fixed phase change system and lipophilic shape-fixed phase change system were mixed in a ratio of 3:7 and packaged in an aluminum foil bag to obtain an energy grid with phase change characteristics.
[0045] Figure 3 This is the DSC curve of the phase change energy grid in Example 2, with a phase change temperature of 24° C. and a phase change enthalpy of 157 J / g, which has a suitable phase change temperature and a high phase change enthalpy.
[0046] Comparative Example:
[0047] Sodium sulfate decahydrate and disodium hydrogen phosphate dodecahydrate were weighed in a mass ratio of 6:4, heated and stirred at 50°C for 1 hour to mix the two uniformly, and the phase change substrate was compounded with polyvinyl alcohol-modified diatomaceous earth, wherein the mass ratio of the phase change substrate to the polyvinyl alcohol-modified diatomaceous earth was 80:10.
[0048] The lipophilic shaped phase change system and ratio are consistent with those in Example 2. The internal material of the obtained energy pack will have fluidity when it is higher than the phase change temperature. After 50 cold and hot cycles, the enthalpy value is greatly reduced (from 157.8 J / g to 109.4 J / g, Figure 4), and the problem of bulging occurred, and the cycle stability, durability and practicality were significantly lower than those of Example 2. However, the energy pack of Example 2 remained in its original state after 100 cycles, and the enthalpy value did not decrease significantly, which was because the addition of the additive could reduce its phase separation, water loss and fluidity problems.
[0049] Embodiment 3-8
[0050] The encapsulating bags were replaced with tin foil bags, copper foil bags, PET bags, PE bags, polytetrafluoroethylene bags, and polypropylene bags, respectively, and other conditions were consistent with those in Example 1, to obtain corresponding energy grids.
[0051] Examples 9-13
[0052] The ratios of the hydrophilic shape-fixed phase change system to the shape-fixed phase change system in Example 1 were respectively changed to 4:6, 5:5, 6:4, 7:3, and 8:2, and the other conditions were consistent with Example 1, and the corresponding energy grids were obtained.
[0053] Examples 14-21
[0054] The supporting materials of the hydrophilic shaped phase change system in Example 1 were replaced with porous silica modified with polyvinyl alcohol, expanded vermiculite, expanded perlite, expanded graphite, activated carbon, porous carbon, bentonite, and porous ceramics, respectively, and the other conditions were consistent with Example 1, and the corresponding energy grids were obtained.
[0055] Examples 22-29
[0056] The supporting materials of the lipophilic shaped phase change system in Example 1 were replaced with porous silica modified by PDMS vapor deposition, expanded vermiculite, expanded perlite, expanded graphite, activated carbon, diatomaceous earth, bentonite, and porous ceramics, respectively. Other conditions were consistent with Example 1, and the corresponding energy grids were obtained.
[0057] Examples 30-34
[0058] The sodium alginate auxiliary agent in the hydrophilic shape-fixing phase change system in Example 2 was replaced with carboxymethyl cellulose, xanthan gum, carrageenan, polyacrylic acid, and sodium polyacrylate, respectively, and other conditions were consistent with Example 2 to obtain the corresponding energy grid.
[0059] Examples 35-55
[0060] The potassium sorbate adjuvant in Example 2 was replaced with dimethyl fumarate, diethyl fumarate, dibutyl fumarate, fumaric acid, benzoic acid, sodium benzoate, para-chloro-m-xylenol, salicylanilide, tetrachlorophenol, pentachlorophenol, sorbic acid, chloroacetic acid, halogenated phenoxyacetic acid, alkyl thiocyanate, halogenated salicylic acid, thiosalicylic acid, sodium chlorite, potassium iodide, boric acid, potassium pyrosulfite, and sodium nitrite, respectively, and the other conditions were consistent with those in Example 2 to obtain the corresponding energy grid.
[0061] Examples 56-75
[0062] The phase change substrates in the hydrophilic shape-fixing phase change system in Example 1 were replaced with sodium carbonate decahydrate / sodium sulfate decahydrate 4:6, calcium chloride hexahydrate / sodium hydrogen phosphate dodecahydrate 6:4, sodium acetate trihydrate, copper sulfate heptahydrate / magnesium sulfate heptahydrate 5:5, dodecanoic acid / palmitic acid 3:7, stearic acid, polyethylene glycol 6000, polyethylene glycol 10000, polyethylene glycol 20000, tetradecanoic acid / stearic acid 5:5, xylitol, sorbitol, barium hydroxide octahydrate, potassium aluminum sulfate dodecahydrate, dodecanol, tetradecanol, hexadecanol, octadecanoic acid, hexadecanol / stearic acid 3:7, hexadecanol / stearic acid / palmitic acid 3:3:4, the additives were 2% sodium metasilicate nonahydrate, 1% carboxymethyl cellulose and 2% potassium sorbate, and the other conditions were consistent with Example 1 to obtain the corresponding energy grid.
[0063] Examples 76-92
[0064] The phase change substrates in the lipophilic shape-fixing phase change system in Example 1 were replaced with tetradecane, hexadecane, octadecane, eicosane, erythritol tetrapalmitate, galactitol hexapalmitate, galactitol hexastearate, tristearin, tripalmitin, trimyristin, butyl stearate, soybean oil, corn oil, peanut oil, rapeseed oil, olive oil, and castor oil, respectively, and the other conditions were consistent with those in Example 1, and the corresponding energy lattices were obtained.
[0065] Examples 93-96
[0066] The phase change substrates in the lipophilic shaped phase change system in Example 1 were replaced with tristearin / tripalmitin 2:8, tristearin / trimyristin 4:6, soybean oil / corn oil / rapeseed oil 2:3:5, and octadecane / eicosane 5:5, respectively, and the other conditions were consistent with Example 1, and the corresponding energy lattices were obtained.
[0067] Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for those skilled in the art to modify the technical solutions described in the aforementioned embodiments, or to make equivalent substitutions for some of the technical features therein. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A new phase change energy grid, characterized in that: The phase-change energy grid uses a powdered composite shaped phase-change material with thermal energy storage performance encapsulated in an encapsulation bag; The composite shape-fixed phase change material is obtained by compounding a hydrophilic shape-fixed phase change system and a lipophilic phase change system, wherein the hydrophilic shape-fixed phase change system and the lipophilic phase change system respectively include a modified support skeleton material, a phase change substrate and an additive; The ratio of the hydrophilic shaped phase change material to the lipophilic phase change system in the composite shaped phase change system is 2:8~8:2, wherein the mass proportion of the modified support skeleton material is 30%~1%, the mass proportion of the phase change substrate is greater than or equal to 50% and less than 99%, and the proportion of the auxiliary agent is greater than zero and less than or equal to 20%.
2. The novel phase change energy grid according to claim 1 is characterized in that: The packaging bag is one of an aluminum foil bag, a tin foil bag, a copper foil bag, a PET bag, a PE bag, a polytetrafluoroethylene bag, and a polypropylene bag.
3. The novel phase change energy grid according to claim 1 is characterized in that: The modified support skeleton material includes a hydrophilic modified support skeleton and an oleophilic modified support skeleton. The hydrophilic modified support skeleton is used in the hydrophilic shaped phase change material, and the oleophilic modified support skeleton is used in the oleophilic phase change system. The modification methods include surface sintering, acid-base reaction, chemical grafting and gas phase reaction.
4. The novel phase change energy grid according to claim 3 is characterized in that: The modified supporting skeleton material is one or more of porous silica, expanded vermiculite, diatomaceous earth, expanded perlite, expanded graphite, activated carbon, porous carbon, bentonite, and porous ceramics that have been hydrophilically modified or lipophilically modified.
5. The novel phase change energy grid according to claim 1 is characterized in that: The phase change substrate is a hydrophilic phase change substrate and a lipophilic phase change substrate. The hydrophilic phase change substrate is one or more of sodium carbonate decahydrate, sodium sulfate decahydrate, calcium chloride hexahydrate, disodium hydrogen phosphate dodecahydrate, sodium acetate trihydrate, copper sulfate heptahydrate, magnesium sulfate heptahydrate, disodium hydrogen phosphate heptahydrate, barium hydroxide octahydrate, and potassium aluminum sulfate dodecahydrate; the lipophilic phase change substrate is one or more of paraffin, tetradecane, hexadecane, octadecane, eicosane, decanoic acid, dodecanoic acid, tetradecanoic acid, pentadecanoic acid, palmitic acid, stearic acid, dodecanol, tetradecanol, hexadecanol, octadecyl alcohol, polyethylene glycol with a molecular weight of 200 to 20,000, xylitol, sorbitol, erythritol tetrapalmitate, galactitol hexapalmitate, galactitol hexastearate, tristearin, tripalmitin, trimyristin, butyl stearate, soybean oil, corn oil, peanut oil, rapeseed oil, olive oil, and castor oil.
6. The novel phase change energy grid according to claim 1 is characterized in that: The auxiliary agent is one or more of water, carboxymethyl cellulose, sodium carboxymethyl cellulose, sodium alginate, xanthan gum, carrageenan, polyacrylic acid, sodium polyacrylate, sodium metasilicate nonahydrate, dimethyl fumarate, diethyl fumarate, dibutyl fumarate, fumaric acid, benzoic acid, sodium benzoate, para-chloro-meta-xylenol, salicylanilide, tetrachlorophenol, pentachlorophenol, sorbic acid and its salts, chloroacetic acid, halogenated phenoxyacetic acid, alkyl thiocyanate, halogenated salicylic acid, thiosalicylic acid, sodium chlorite, iodide, boric acid and its salts, sulfites and pyrosulfites, and sodium nitrite.
7. The method for preparing the novel phase change energy lattice according to any one of claims 1 to 6, characterized in that: The following steps are involved: (1) The hydrophilic phase change substrate and the lipophilic phase change substrate are heated and melted at 50 to 80° C., respectively, and magnetically stirred for 0.5 to 2 h to form a uniform liquid; (2) adding the auxiliary agent and the hydrophilic modified supporting skeleton material to the hydrophilic phase change substrate in the molten state in step (1), and the hydrophilic modified skeleton material adsorbs the hydrophilic phase change substrate; adding the auxiliary agent and the lipophilic modified supporting skeleton material to the lipophilic phase change substrate in the molten state in step (1), and the lipophilic modified skeleton material adsorbs the lipophilic phase change substrate; stirring continuously during the process to ensure uniform mixing; (3) placing the composite materials in step (2) in a vacuum drying oven at 50°C to 80°C and heating them to obtain a hydrophilic shape-fixed phase change system and a lipophilic phase change system; (4) The prepared hydrophilic shape-fixing phase change system and lipophilic phase change system are mixed evenly in proportion, put into a packaging bag, and sealed with a hot press to obtain a new phase change energy grid.
Citation Information
Patent Citations
Phase-change ceramic grain and preparation method thereof
CN103509529A
Preparation method of porous matrix composite phase change materials for recycling wide-temperature range afterheat
CN104449589A
Phase change energy storage composite microcapsule and manufacturing method thereof
CN105219352A
Preparation method for coolant for refrigerating transportation box
CN107573900A
Flexible lightweight shape-stabilized phase change energy storage piece and preparation method thereof
CN107760274A